The Effect of Ethanol Extract of Piper nigrum L. Fruit on Reproductive System in Adult Male Wistar Rats: A Study of FSH, LH, Testosterone Level and Spermatogenic Cells - Ekaputri, Tia Wida; Sari, Ika Puspita; Rizal, Dicky Moch. (Indonesian Journal of Pharmacy, 2018)
Exploration to find out new natural contraceptive agent for male is still being developed. Black pepper (Piper nigrum L.) and its main alkaloid piperine have potential antifertility because of sitotoxic and hormonal effects. The aim of this study is to find out the effect of ethanolic extract of black pepper (Piper nigrum L.) fruit of on reproductive hormone serum level, sperm quality, and spermatogenic cell populations in adult male Wistar rat. Twenty five male rats were divided into five groups consisting of two control group, i.e. K(-) (Na-CMC 0.5%), K(+) (finasteride 0.45mg/kg BW), and three groups received different doses of black pepper fruit ethanolic extract, i.e. D(1) (3.33mg/kg BW), D(2) (6.66mg/kg BW) and D(3) (13.32mg/kg BW) respectively. The treatment were given to each group for 55 days. Reproductive parameters were measured, including serum level of reproductive hormones (FSH, LH, dan testosteron), quality of cauda epididymal sperm (spermatozoa concentration, motility and morphological abnormality), spermatogenic cell populations (primary spermato-cyte and spermatid count) and seminiferous tubules diameter. Ethanol extract of black pepper fruit at doses of 3.33mg/kg BW, 6.66mg/kg BW, and 13.32mg/kg BW increased serum FSH level. Extract at dose of 13.32mg/kg BW decreased serum LH level, while extract at doses of 6.66mg/kg BW and 13.32mg/kg BW decreased serum testosterone level. The number of primary spermatocytes, spermatozoa concentration, and spermatozoa motility were decreased by administration of ethanol extract of black pepper fruit with dose of 6.66mg/kg BW and 13.32mg/kg BW. Ethanol extract of black pepper fruit at dose of 6.66mg/kg BW and 13.32mg/kg BW had a negative impact on the male reproductive system and showing potential antifertility in maleÂ rat.